Sueño de lectores - Hernández, Alejandra Fabiana (2024)
Autores Carátulas: Gastón Ludueña, Nicolás Choque, Abril Ireba, Consuelo Rotondo, lara Espir. Tapas: Seculin Glur Guadalupe Abril. Estampas: Dughetti Brunella, Villarroel Gabriel Agustín, Florencia Bernelli, Oliver lizasu, Lautaro Zuleta, Giulietta Fiorela Paolucci, Amara Caballero, Aguirre Garro Melina, Daya Puigchouhy, Pérez Julieta, Seculin Glur Guadalupe Abril. Intervenciones: Villarroel Gabriel Agustín, Oliver Lizasu, Giulietta Fiorela Paolucci, Ander Luca Leonardo, Sofía Flores, Milagros Salerno, Melo Valentina, Martina Chinchilla, Milagros Moroz. Pegado: Albarracín Guadalupe, Angélica Sánchez Ríos, Brenda Díaz, Martina Chinchilla, Piccinini Juan Tomás, Lara Alazraki, María Valentina Mecodangelo, Luciana Pérez, Tiziano Di Forte, Milagros Moroz Equipo de cátedra: Alejandra Fabiana Hernández, Lucía Álvarez Pérez, Nadine Madelon, Laura Lucero, Belén Canesini, Ignacio Font. Ayudantes alumnes: Juan Blanco, Julián Bravo, Lucía Bustos Brunetti, Kiara Figueroa, Florencia Gieco, Matilde Leblebidjian, Moira Michelik, Anabella Ugarte, Ana Paula Villarruel, Erika Wayar.